Synthesis of non-symmetrical alkynylpyridines by chemoselective Sonogashira cross-coupling reactions. Issue 40 (4th October 2019) - Rivera, Rodisnel Perdomo; Ehlers, Peter; Ohlendorf, Lars; Ponce, Marian Blanco; Rodríguez, Eugenio Torres; Langer, Peter
Abstract: 4-Bromo-2, 3, 5-trichloro-6-iodopyridine was studied as a new substrate in chemoselective Sonogashira reactions. This approach provides an efficient access to non-symmetrical mono-, di-, tri- and pentaalkynylated pyridines in good yields. Selected pentaalkynylated pyridines were studied with regard to their UV/Vis- and emission properties showing moderate to high fluorescence quantum yields. Graphical abstract: Image 1 Highlights: First Sonogashira reactions of 4-bromo-2, 3, 5-trichloro-6-iodopyridine. Synthesis of novel non-symmetrical mono-, di-, tri- and pentaalkynylated pyridines in good yields. Moderate to high fluorescence quantum yields.